The healing effects of prp and thymoquinone on dss induced inflammatory bowel disease in rats (Annals of Medical Research, 2021)
Aim: Crohn's disease and ulcerative colitis are included in inflammatory bowel disease (IBD). The study aimed to compare the healing effects of two promising therapeutic agents: Platelet Rich-Plasma and Thymoquinone (TQ) on DSS induced IBD.Materials and Methods: The animals were divided into three groups as IBD (n=10), PRP treatment (n=10) and TQ treatment (n=10). Experimental IBD was initiated through the oral intake of 5% Dextran Sodium Sulfate (DSS) in drinking water. PRP (0.5 cc) and thymoquinone dissolved in distilled water (100mg/kg) were daily administered rectally to PRP treated group animals for seven days. All animals were sacrificed and rectal tissue calprotectin, lactoferrin and hydroxyproline levels were assessed on the seventh day. Total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) levels were statistically compared.Results: Rectal tissue calprotectin, lactoferrin and hydroxyproline levels were higher in the IBD group (p